PERAN ORGANISASI PASAR PELAYARAN DALAM MENINGKATKAN DAYA SAING TRANSPORTASI LAUT - Laoderamiu; Eliyanti Agus Mokodompit (STIE ENAM ENAM KENDARI, 2025)
This study aims to examine the role of shipping market organizations in improving the competitiveness of maritime transportation in Kendari City, with a focus on adaptive strategies implemented to address the challenges of globalization and environmental regulations. The research approach uses a qualitative case study method, with data collection through semi-structured interviews with key players in the shipping market and analysis of supporting documents. Data were analyzed using thematic techniques to identify patterns and strategic themes contributing to enhanced competitiveness. Key findings indicate that coordination among market actors through regular forums, adoption of digital technology in fleet management, and adaptation to carbon emission regulations are effective key strategies. Additionally, this study highlights the importance of infrastructure development and human resource capacity as enablers of these strategies' success. The research results expand the literature by providing a contextual perspective on the adaptation of shipping market organizations in developing medium-sized ports. In conclusion, shipping market organizations in Kendari play a significant role in managing market dynamics and supporting the sustainability of maritime transportation. This study suggests strengthening coordination mechanisms and accelerating digitalization as future development priorities. Recommendations for future research include the use of broader quantitative methods to objectively measure the impact of the strategy.